Revisiting revenue contingent loans for drought relief: government as risk manager1. (31st May 2017) - Botterill, Linda Courtenay; Chapman, Bruce; Kelly, Simon
Abstract : It is clear that Australian governments will provide assistance to farmers in drought, which is a rational political judgement supported by recent survey work suggesting strongly the pervasive existence among voters of agrarian sentiment. In this context, a reasonable question relates to what forms of assistance are most equitable for taxpayers and also have desirable properties for farm businesses. In this study it is argued that traditional and current approaches to drought assistance are not equitable and do not provide sufficient protection to farmers from default and thus insolvency risk. But there is an instrument available to government which can be designed to minimise taxpayer subsidies while at the same time delivering insurance for farmers against default: a Revenue Contingent Loan (RCL). Following the principles inherent in the Higher Education Contribution Scheme, a RCL is financial assistance repaid contingent on a farm's capacity to pay, meaning that loan defaults can be avoided. We model the revenue streams associated with a hypothetical loan of this type and illustrate the advantages for a farm business of these kinds of debt.